Hemophilus meningitis – Current Aspects of Epidemiology and Prevention: a Descriptive Review - M. I. Gritsay; I. S. Koroleva; M. A. Koroleva (Эпидемиология и вакцинопрофилактика)
Relevance. H. influenzae is a common cause of bacterial meningitis in children worldwide. Significant data have been accumulated worldwide on the use of H. influenzae type b conjugate vaccines over the past three decades. In the Russian Federation, constant monitoring of hemophilic meningitis is carried out, but data on the incidence of hemophilic infection are limited.Target. To consider global changes in the epidemiology of invasive forms of H. influenzae in the world and in the Russian Federation.Conclusions. The use of conjugate vaccines has resulted in a steady decline in invasive Hib infections. However, there has been a significant increase in invasive infections with non-typeable H. influenzae and non-b serotypes. In the Russian Federation, the incidence of meningitis caused by H. influenzae does not tend to increase or decrease; the majority of cases occur in children under 5 years of age.